Biosynthesis of the transferrin receptor in rabbit reticulocytes. - T M Cox; M W O'Donnell; P Aisen; I M London (The Journal of Clinical Investigation, 1985)
These studies were performed to determine whether the reticulocyte can synthesize its own transferrin receptor and, if so, whether synthesis is subject to translational control by intracellular heme. Reticulocytosis (20-35%) was produced by bleeding rabbits and the washed cells were incubated for 1-4 h at 37 degrees C in buffered nutritional medium containing L-[35S]methionine. After washing and detergent lysis in the presence of protease inhibitors, supernatant reticulocyte extracts were analyzed for transferrin receptors by immunoprecipitation with specific ovine receptor antibody raised against denatured rabbit transferrin receptor. Immunoprecipitates were analyzed by SDS-gel electrophoresis and fluorography. Antibody, but not preimmune sheep immunoglobin, consistently precipitated a 35S-labeled protein with an Mr of 90,000 (reduced), coincident with bona fide receptor subunits purified by ligand-affinity chromatography. Incorporation of radioactive methionine was exclusively associated with receptor in reticulocyte stroma, and nascent receptor was not detected on free polyribosomes. Incorporation of radioactivity in the receptor moiety accounted for 0.1-0.2% of total incorporation into TCA insoluble cell protein. Treatment of the cells with 40 micrograms/ml cycloheximide markedly inhibited amino acid incorporation into the receptor, thus indicating de novo synthesis of receptor protein. On treatment of reticulocytes with 4,6 dioxoheptanoate to induce heme deficiency by diminishing the formation of intracellular heme, synthesis of the receptor was inhibited by greater than 50%; synthesis was restored to control rates on addition of 50 microM exogenous hemin. These findings indicate that the reticulocyte retains receptor mRNA and that synthesis of the receptor in erythroid cells is subject to translational regulation by intracellular heme. Images